DOES SUKUK FINANCING PROMOTE ECONOMIC GROWTH? AN EMPHASIS ON THE MAJOR ISSUING COUNTRIES - Abdelghani ECHCHABI; Hassanuddeen ABD.AZIZ; Umar IDRISS (Türkiye İslam İktisadı Dergisi, 2016)
For the past few decades, Islamic finance has imposed itself as a viable alternative / complementary system to the long existing conventional financial system. Nevertheless, recent research has claimed that Islamic finance as it is currently practice, does not promote economic growth. Hence, the objective of this study is to empirically test this claim, by examining the potential effect of Islamic finance in the specific form of Sukuk issuance on the economic growth represented by three proxies, namely, Gross Domestic Product (GDP), Gross Capital Formation (GDP) and trade activities. The data covers not only GCC (Gulf Cooperation Council), but also other countries including Malaysia, Indonesia, Turkey, Pakistan, Singapore, China, Brunei, Kazakhstan, Germany, United Kingdom (UK), The Gambia and France. The data were collected from the Islamic Finance Information Services (IFIS) and the World Bank databases, and were subsequently analysed through Toda and Yamamoto Granger Non Causality test. Accordingly, the findings indicated that the Sukuk issuance had an influence on the GDP and GCF only when all the countries were pulled together, otherwise no effect was identified for Saudi Arabia and the GCC.